Mathematics Literacy Skill Based on Self-directed Learning on Meaningful Instructional Design Based Outdoor Learning - Arifani, Hilda; Wardono, Wardono; Cahyono, Adi Nur (Universitas Negeri Semarang, 2021)
This research aims to describe mathematics literacy skills seen from self-directed learning of X graders. This mixed method research used sequential explanatory design. The subjects were selected based on each self-directed learning category. The category consisted of high, moderate, and poor by using purposive sampling to determine the sample. The findings showed that descriptive learning of mathematics literacy skill seen from self-directed learning of the students was varied based on their characteristics. It was shown by 9 students with high self-directed learning with 2 of them high category, 6 moderate category, and 1 poor category. From 24 moderate self-directed learning students, 2 of them were categorized high, 21 moderate, and 1 poor category. From 3 poor self-directed students, 1 of them was categorized high while the others were categorized poor.